Once Bound (A Riley Paige Mystery-Book 12) - Blake, Pierce (Lukeman Literary, 2018)
"A masterpiece of thriller and mystery! The author did a magnificent job developing characters with a psychological side that is so well described that we feel inside their minds, follow their fears and cheer for their success. The plot is very intelligent and will keep you entertained throughout the book. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) ONCE BOUND is book #12 in the bestselling Riley Paige mystery series, which begins with the #1 bestseller ONCE GONE (Book #1)-a free download with over 1,000 five star reviews! In this heart-pounding thriller, women are being found dead on train tracks across the country, forcing the FBI into a mad race against time to catch the serial killer. FBI Special Agent Riley Paige may have finally met her match: a sadistic killer, binding victims to the tracks to be killed by incoming trains. A killer smart enough to evade capture across many states-and charming enough to go unseen. She soon learns it will require all of her faculties to enter into his sick mind-a mind which she unsure she wants to enter. And all with a final twist that is so shocking, even Riley could not expect it. A dark psychological thriller with heart-pounding suspense, ONCE BOUND is book #12 in a riveting new series-with a beloved new character-that will leave you turning pages late into the night. Book #13 in the Riley Paige series will be available soon.
Keywords: Krimi, detektivky